THE INFLUENCE OF LEARNING MOTIVATION, LEARNING STYLE, PEERS ON STUDENTS' ECONOMIC LEARNING INTEREST - Fasya, Salwa Ghina; Nurdin, Nurdin; Suroto, Suroto (Soedirman Economics Education Journal, 2023)
This study aims to determine the effect of learning motivation, learning styles and peers on students' interest in learning economics. This study uses quantitative descriptive research methods with a survey approach and ex post facto. The population used in the study were all XII social studies students with a total of 63 students. The population used in the study were all XII social studies students with a total of 63 students. The sampling technique uses saturated samples which means that the entire population is used as a sample. Data collection techniques used are interviews, observations, questionnaires, and documentation. Hypothesis testing is done through partial regression analysis test (t test) and simultaneous regression analysis test (f test). Based on the results of hypothesis testing using partial tests, it was found that each independent variable, namely learning motivation, learning style, and peers, had a positive influence on student interest in learning. Based on simultaneous tests, overall learning motivation, learning styles, and peers have an effect on students' interest in learning economics. In order for students' interest in learning economics to be as expected by the teacher, the teacher should also pay attention to variables that can affect students' interest in learning such as learning motivation, learning styles and peers.